2022
DOI: 10.3389/fpls.2022.1043378
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the main health-promoting compounds and antioxidant activity of different organs of Wasabi (Eutrema japonicum) from two producing areas

Abstract: Wasabi (Eutrema japonicum), also known as Japanese horseradish, is a perennial herb widely used in Japanese cuisine for its special flavour. The health-promoting phytochemicals and antioxidant capacity of four organs (leaf, petiole, rhizome, and root) of two cultivars (Chuankui–1 and Chuankui–2) of wasabi from two producing areas, Leibo and Guangyuan in Sichuan Province, China, were investigated in this study. The results showed that leaves were rich in pigments, soluble protein, ascorbic acid, and total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Glucoibervirin, glucohesperin, and glucosequerellin were also present in considerable quantities in the wasabi extract; however, their contents were much lower than that of sinigrin. Previous studies have consistently identified sinigrin as the most abundant GSL in various wasabi plant parts, including the leaves, flowers, seeds, roots, and rhizomes [ 26 , 30 – 32 ]. Our findings are aligned with previous study, indicating a higher abundance and accumulation of sinigrin in the rhizomes and roots than in the leaves and petioles [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucoibervirin, glucohesperin, and glucosequerellin were also present in considerable quantities in the wasabi extract; however, their contents were much lower than that of sinigrin. Previous studies have consistently identified sinigrin as the most abundant GSL in various wasabi plant parts, including the leaves, flowers, seeds, roots, and rhizomes [ 26 , 30 – 32 ]. Our findings are aligned with previous study, indicating a higher abundance and accumulation of sinigrin in the rhizomes and roots than in the leaves and petioles [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have consistently identified sinigrin as the most abundant GSL in various wasabi plant parts, including the leaves, flowers, seeds, roots, and rhizomes [ 26 , 30 – 32 ]. Our findings are aligned with previous study, indicating a higher abundance and accumulation of sinigrin in the rhizomes and roots than in the leaves and petioles [ 32 ].…”
Section: Resultsmentioning
confidence: 99%